Protection of access to essential treatment for people living with HIV/AIDS in Uganda from a human rights perspective - Twinomugisha, Ben Kiromba (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2005.